PENGARUH BAURAN PEMASARAN (MARKETING MIX) 7P TERHADAP KEPUASAN KONSUMEN - Kaunang, William; Muzendi, Agustina Mori; Ardha Puspita Sari (Sosio Agri Papua, 2022)
The scope of this research includes: (1) The study takes the case of a cafe business, namely Wilchof Cafe. The main product is coffee as processed from the coffee plant, (2) Marketing mix attributes are analyzed using the 7P mix reference, namely product, price, promotion, people, place, physical evidence and process, (3) The focus of this research is on consumer opinions/perceptions on the attributes of the marketing mix that is not limited to the period before and after the pandemic, (4) The selection of respondents uses 2 methods, offline and online. The research method uses quantitative methods with a survey approach. Sources of data used in this study are primary and secondary data. The sampling method used non-probability sampling method with accidental sampling and purposive sampling techniques. Respondents who were used as samples were 45 people. The results of data processing with Spearman Rank correlation analysis using SPSS obtained results between the 7P marketing mix and consumer satisfaction. The 7P marketing mix affects the level of consumer satisfaction at Wilchof Cafe, namely physical evidence (0.760) in a strong relationship, product (0.672) in a strong relationship, people (0.654) in a strong relationship, process (0.525) in a moderate relationship, promotion (0.467) in a moderate relationship, place (0.370) in a low relationship and price (-0.070) in a very low relationship. Almost all variables have a positive direction except price, because consumers who visit do not see it in terms of price, they will still buy the product.